2019
DOI: 10.1108/ijppm-03-2018-0087
|View full text |Cite
|
Sign up to set email alerts
|

Lean culture: a comprehensive systematic literature review

Abstract: Purpose The purpose of this paper is to assess the level of pragmatic ambiguity (PA) lean culture has currently in the manufacturing and service literature. Design/methodology/approach A comprehensive systematic review of academic (journals, books and theses) and commercial literature was undertaken drawn from a six databases search of two keywords (“lean” and “culture”) and related citations. Findings A total sample of 1,066 references (678 academic papers, 121 books, 103 theses and 164 commercial documen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 34 publications
0
64
0
Order By: Relevance
“…Changes at the organizational level, following lean thinking, also require a cultural adaptation [62]. Organizational and cultural changes result in direct impacts on clinical aspect of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Changes at the organizational level, following lean thinking, also require a cultural adaptation [62]. Organizational and cultural changes result in direct impacts on clinical aspect of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Lean production (LP) is an established field of practice and a maturing scientific discipline, as shown by the several literature reviews that have made sense of the growing body of knowledge (e.g. Dorval et al, 2019;Sangwa and Sangwan, 2018). However, this widespread use of lean has contributed to misunderstandings, which can be exemplified by the various definitions of LP, its core principles and practices (Antony et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Success in modern management practice implementation requires more than use of tools and techniques. Dorval et al (2019) comprehensively reviewed lean culture literature and found that organization and culture perspectives should be determined for effective lean implementation. Similarly, Zhang and Cao (2018) reported that many SCR fail because of incompatible organizational cultures and the organizational complexities.…”
Section: Introductionmentioning
confidence: 99%